Ανάλυση χρονοσειρών από δεδομένα Landsat 8 για την αξιολόγηση του αλγορίθμου Fmask - Γαλανάκης, Δημήτριος (Εθνικό Μετσόβιο Πολυτεχνείο. Σχολή Αγρονόμων και Τοπογράφων Μηχανικών. Τομέας Τοπογραφίας. Εργαστήριο Τηλεπισκόπησης, 2016)
The necessity for monitoring and understanding of the trends and dynamics of various ecosystems, concerning the Land Use/ Land Cover, becomes more urgent day by day due to the constantly increasing worldwide social and economical needs. The modeling of these trends and the extraction of usefull data from them is now attainable thanks to the large volume of remote sensing Open Data that are now available and provide long, continuous observations of the Earths surface in various regions of the spectrum. Typical example of such data is the recently opened archive of the Landsat Programm, which provides high spatial resolution data for more than 43 years. However, the development of methods that effectively exploit these remote sensing data time series is an open problem.